Mucus-targeting therapies of defective mucus clearance for cystic fibrosis: A short review. (August 2022) - Figueira, Miriam Frankenthal; Ribeiro, Carla M.P.; Button, Brian
Abstract: In the lungs, defective CFTR associated with cystic fibrosis (CF) represents the nidus for abnormal mucus clearance in the airways and consequently a progressive lung disease. Defective CFTR-mediated Cl − secretion results in altered mucus properties, including concentration, viscoelasticity, and the ratio of the two mucins, MUC5B and MUC5AC. In the past decades, therapies targeting the CF mucus defect, directly or indirectly, have been developed; nevertheless, better treatments to prevent the disease progression are still needed. This review summarizes the existing knowledge on the defective mucus in CF disease and highlights it as a barrier to the development of future inhaled genetic therapies. The use of new mucus-targeting treatments is also discussed, focusing on their potential role to halt the progress of CF lung disease.